Cutaneous Mucormycosis Co-infection in a Patient with COVID-19 - Raham Rahgoshai; Peter Goldberg; Rayhaneh Rahgoshai; Shadi Zain (European Medical Journal)
Mucormycosis is a life-threatening fungal infection usually seen in patients who are immunocompromised; however, to date, it has been rarely described in patients with COVID-19, although more recently, reports from India have described an increased incidence of these infections. This report describes a patient with COVID-19 who developed a fatal dermatologic mucormycosis infection. The patient, whose history included therapy for diffuse large B-cell lymphoma, had an incidental positive screening test for COVID-19 in February 2021 after exposure to a family member who had tested positive. They then presented to the emergency room a few weeks later exhibiting progressive dyspnoea and fever. A CT scan of the chest revealed ground glass opacities. They were intubated approximately 2 weeks later and their course was complicated by renal failure, for which continuous renal replacement therapy was started, and by refractory hypoxaemic and hypercapnic respiratory failure in which they were placed on venovenous extracorporeal membrane oxygenation. During their course in the intensive care unit (ICU), they developed a right thigh haematoma, thought to be related to the previous insertion of a femoral arterial pressure monitoring catheter. Several days before the patient’s death, the wound noted to be covered by a brown-black eschar was cultured on April 30 and returned positive for Rhizopus oryzae and Staphylococcus epidermidis on May 5. The patient was immediately started on liposomal amphotericin and posaconazole and taken urgently taken to the operating room for a radical debridement. Unfortunately, their post-operative course was characterised by fulminant haemodynamic collapse and multiple system organ failure, from which the patient died.